KARAKTERISTIK KUALITATIF DAN KUANTITATIF SAPI PERANAKAN ONGOL DAN SAPI SIMPO JANTAN PADA GIGI SERI BERGANTI 2 DI KECAMATAN TERBANGGI BESAR KABUPATEN LAMPUNG TENGAH - Dhita, Nandia Thara; Hamdani, M. Dima Iqbal; Adhianto, Kusuma (Jurnal Riset dan Inovasi Peternakan, 2017)
Research was conducted to determine the qualitative and quantitative characteristics of PO cattle and Simpo cattle males in permanent teeth 2 at District Terbanggi Besar, Central Lampung. Research was conducted on 100 PO cattles and 100 Simpo cattles, sample observation is determined by purposive sampling.  Research used survey method from August to October 2016. The results of research at District Terbanggi Besar showed the quantitative characteristic of PO cattle in permanent teeth 2 trait body weight (340,36±46,21 kg), chest circumference (154,84±9,51cm), body length (111,94±4,46cm), and shoulder height (127,48±4,05cm) had significant differences with Simpo cattle in permanent teeth 2 on average weight body (387,48±46,43kg), chest circumference (167,80±7,98cm), body length (117,54±7,00cm), and shoulder height (130,46±3,46cm) at District Terbanggi Besar. Qualitative characteristic such as skin color Simpo cattle in permanent teeth 2 are brown white (62%), white brown black (14%), white black (24%), sagged (100%), humped (52%), no hump (48% ), horns (52%), and no horns (48%). Keywords: PO Cattle, Simpo Cattle, qualitative and quantitative characteristics, body weight, and body measurements.